(untitled) (Communications in Computational Physics, 2014)
In this paper, the mechanisms of material removal in chemical mechanical polishing (CMP) processes are investigated in detail by the smoothed particle hydrodynamics (SPH) method. The feature-scale behaviours of slurry flow, rough pad, wafer defects, moving solid boundaries, slurry-abrasive interactions, and abrasive collisions are modelled and simulated. Compared with previous work on CMP simulations, our simulations incorporate more realistic physical aspects of the CMP process, especially the effect of abrasive concentration in the slurry flows. The preliminary results on slurry flow in CMP provide microscopic insights on the experimental data of the relation between the removal rate and abrasive concentration and demonstrate that SPH is a suitable method for the research of CMP processes.